What Does your Partner Want? Using a Gender Equality Lens to Assess Partner Support and Involvement in Family Planning in Uganda - Olapeju, Bolanle; Odeke, Paul; Nalukwago, Judith; Mugabe, Pallen; Bufumbo, Leonard; Kimbowa, Musa; Kayongo, Emmanuel; Naibere, Mabel; Nanyonga, Nanah; Mugahi, Richard; Bakyaita, Tabley; Kabanda, Richard (Research Square, 2022)
While partner involvement in health-related decision-making is linked with positive health behaviors, a key gap in the literature exists on how this construct should be measured and the specific ways men and women in Uganda perceive partner support in the context of family planning. The USAID-funded Social and Behavior Change Activity (SBCA) in Uganda explored the differences in male versus female priorities in the decision-making considerations and preferred measures of partner support related to family planning in order to design contextually relevant solutions.
Keywords: partner; gender equality lens; Family Planning